Synthesis, antibacterial activity and molecular docking study of vanillin derived 1, 4-disubstituted 1, 2, 3-triazoles as inhibitors of bacterial DNA synthesis. Issue 11 (November 2019) - Hussain, Mumtaz; Qadri, Tahir; Hussain, Zahid; Saeed, Aamer; Channar, Pervaiz Ali; Shehzadi, Syeda Aaliya; Hassan, Mubashir; Larik, Fayaz Ali; Mahmood, Tarique; Malik, Arif
Abstract: Antimicrobial resistance (AMR) compelled scientists in general while pharmacists, chemists and biologists in specific to believe that we could always remain ahead of the pathogens. The pipeline of new drugs is running gasping and the inducements to develop new antimicrobials to address the global problems of drug resistance are weak. In this pursuit, effective endeavours to prepare new anti-bacterial entities is highly wished. The present study demonstrates successful synthesis of a library of 1, 4-disbustituted 1, 2, 3-triazoles (3a-3k) using Click-chemistry concept and anti-their bacterial potential. In this 1, 3-dipolar cycloaddition, the 3-methoxy-4-(prop-2-yn-1-yloxy)benzaldehyde (1) was used as alkyne partner which was synthesized from vanillin and propargyl bromide and further reacted with differently substituted arylpropoxy azides (2a-k ) to furnish series of mono and bis 1, 4-disubstituted-1, 2, 3-triazoles. All the synthesized compounds were characterized spectroscopically and were evaluated for their initial antimicrobial activity. Preliminary results of antibacterial screening revealed that the synthesized compounds have the highest inhibitory effects compare to the control ciprofloxacin. The compounds 3b and 3g were found to be the most active (MIC: 5 μg/mL, MIC: 10 μg/mL respectively) against various strains of gram-positive and gram-negative bacteria. The molecular docking study against 4GQQ protein with synthesized ligands was performed to see the necessary interactions responsible for anti-bacterial activity. The docking analysis of the most potent compound 3g supported the antibacterial activity exhibiting high inhibition constant and binding energy. Abstract : Organic chemistry; Pharmaceutical chemistry, Click chemistry; 1, 4-Disubstituted 1, 2, 3-triazoles; Antibacterial agents; Molecular docking; Thymidylate kinase (TMPK) inhibitors